The Intersection of Digital Art and Artificial Intelligence: New Aesthetic Paradigms and Theoretical Approaches. - Özdemir, Abdulkadir (Electronic Turkish Studies, 2026)
The intersection of digital art and artificial intelligence (AI) constitutes one of the most dynamic cultural and artistic transformation areas of the 21st century. This interaction requires new aesthetic paradigms and theoretical frameworks that fundamentally question the ways art is produced, received, and defined, going beyond mere technical advancement. While in traditional art the artist's intentional expression is central, in AI-based production, algorithmic processes, large datasets, and learning mechanisms become the focus of creativity. This situation leads to the rethinking of fundamental concepts such as "creativity," "originality," and "the artist." Among the new aesthetic paradigms, the "AI aesthetics" or "post-digital aesthetics" emerging from machine learning stands out. This aesthetic is built upon the limits of human intervention, non-deterministic production, generative forms, and data-material transformation. The artwork becomes less a final product and more a manifestation of the dynamic process of algorithm, data, and human-interface interaction. In art, "discovery" and "probability" gain importance over "expression." Theoretical approaches, in turn, necessitate an interdisciplinary perspective to explain this new ground. Post-humanist theory transcends the human-centric understanding of art by focusing on human-machine collaboration. Actor-Network Theory (ANT) analyzes networks in which humans, algorithms, software, and data participate as actors on an equal level. Probabilistic aesthetic theories, based on the statistical foundations of AI, approach art as a practice of making selections from within probability distributions. At the same time, critical theory in this field opens discussions on ethical and political dimensions such as data policies, the reflections of algorithmic biases on aesthetics, and digital labor. In conclusion, the intersection of digital art and AI brings forth a data-based, generative, collaborative, and process-oriented paradigm that transforms the ontological and epistemological foundations of art. This field necessitates not only new artistic forms but also a comprehensive theoretical renewal that will make sense of these forms, challenging traditional art history and criticism.